PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK SEKOLAH DASAR MELLAUI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) - Nisa Inarotul Aulia; Hany Handayani (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2018)
This study aims to determine the increase in the ability to understand the concept of grade V elementary students through the TGT learning model. Quasi experimental research method and Nonequivalent Control Design Group design. Participants in this study were the fourth grade students of SD who were 40 students. Sampling in this study uses Nonprobality and saturated sampling techniques. Data analysis in the study used the ability to understand students' mathematical concepts, and documentation. From the results of the understanding of mathematical concepts ability of elementary school students in Purwakarta experienced a significant increase after obtaining learning with the TGT model. This is evidenced by the results of the calculation of the N-gain test data obtained P-Value (Sig-tailed) of 0.000 0.05. The acquisition of the results of the average value of the experimental class Posttest is 60.25 and the results of the control class average Posttest score are 23.75. This means that an increased understanding of the experimental class mathematical concepts is higher than the control class. Thus it can be concluded that the TGT learning model is recommended as an alternative learning model in improving understanding of the mathematical concepts of elementary students in Purwakarta